POLYPOIDAL CHOROIDAL VASCULOPATHY MANIFESTATION IN EXTRA-AXIAL CAVERNOUS TUMOR: A RARE FINDINGS IN CHRONIC PAPILLEDEMA - Asti, Annisa Kinanti; Agustini, Lukisiari; Firmansjah, Muhammad (International Journal of Retina, 2025)
Introduction: Age-related macular degeneration (AMD) is a leading cause of blindness worldwide. Polypoidal choroidal vasculopathy (PCV), a subtype of neovascular AMD, is characterized by an abnormal branching network of vessels with aneurysmal dilations (polyps). Choroidal neovascularization can also result from chronic disc edema. This case presents a rare occurrence of PCV in a patient with an extra-axial cavernous tumor and explores the best management approach. Case Report: A 43-year-old man presented with an 8-month history of blurry vision in his right eye, double vision on left gaze, and left eye protrusion, accompanied by headaches and occasional nausea. Visual acuity was 2/60 in the right eye and 5/10 in the left improving with pinhole become 5/6.5. RAPD was found in left eye. Funduscopy revealed peripapillary atrophy in both eyes, with exudates in the right macula. OCT showed dome-shaped polyps in both eyes, larger in the right. MRI revealed a left sphenoid meningioma compressing the orbital cavity. The patient was diagnosed with both eyes PCV and compressive optic neuropathy, left eye multiple cranial nerve palsy and dyslipidemia. Intravitreal anti-VEGF injection was planned. Discussion PCV is a subtype of AMD characterized by recurrent serosanguineous detachments. Chronic papilledema, possibly due to intracranial tumors, may lead to visual loss from retinal nerve fiber damage or neovascularization. Chronic posterior globe flattening and choroidal vessel abnormalities likely contributed to PCV development. Conclusion: PCV may result from chronic papilledema due to intracranial tumors. Anti-VEGF therapy offers a viable treatment option, balancing polyp regression and visual acuity stabilization.